(untitled) (International Journal of Humanities and Information Technology, 2025)
Coastal regions are among the most productive agricultural areas globally, yet they face unique challenges due to climate change, salinity intrusion, and social inequalities. Coastal agronomy, the practice of cultivating crops and managing land in coastal zones, plays a critical role in ensuring food security and sustainable livelihoods for millions of people. However, the benefits of coastal agronomy are often unevenly distributed, with marginalized communities frequently excluded from development opportunities. This paper explores the intersection of coastal agronomy and inclusive development, highlighting the potential of agronomic practices to promote equity, sustainability, and resilience in coastal regions. By examining the challenges and opportunities in coastal agriculture, this paper advocates for integrated approaches that prioritize social inclusion, environmental sustainability, and economic empowerment.